Influence Service Quality to Performance Employee and Customer Satisfaction at PT. PBM Adhiguna Son - ainaya asmaralda, zahara; Wijaya, Chandra (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study investigates the impact of service quality on employee performance and customer satisfaction at PT. PBM Adhiguna Son, a company in the maritime logistics sector. The company, facing increased competition in the post-COVID era, strives to improve both its internal performance and customer satisfaction. The research uses a quantitative approach with a descriptive method, employing surveys and interviews to collect data from 75 consumers and various stakeholders. The results show a significant positive relationship between service quality and employee performance, with a coefficient of 0.790 and a p-value of 0.000. Additionally, service quality directly affects customer satisfaction, with a coefficient of 0.903 and a p-value of 0.000. Furthermore, employee performance is positively correlated with customer satisfaction, with a coefficient of 0.412 and a p-value of 0.038. The study also highlights that employee performance mediates the relationship between service quality and customer satisfaction. This research emphasizes the importance of improving service quality and employee performance to enhance customer satisfaction, thereby contributing to the company's long-term success in the competitive market.